Diverse "roof shaped" chiral diamidophosphites: palladium coordination and catalytic applications. (5th January 2022) - Gavrilov, Konstantin N.; Chuchelkin, Ilya V.; Gavrilov, Vladislav K.; Zheglov, Sergey V.; Firsin, Ilya D.; Trunina, Valeria M.; Zamilatskov, Ilya A.; Tyurin, Vladimir S.; Tafeenko, Victor A.; Chernyshev, Vladimir V.; Zimarev, Vladislav S.; Goulioukina, Nataliya S.
Abstract : "Roof shaped" chiral diamidophosphites of various structures and denticities were obtained and tested in Pd-catalyzed asymmetric allylic substitution. Abstract : A series of diamidophosphite ligands of various structures and denticities were synthesized from (11 S, 12 S )-bis(hydroxymethyl)-9, 10-dihydro-9, 10-ethanoanthracene as a "roof shaped" 1, 4-diol. On the basis of these ligands, we obtained three types of Pd(II) allylic complexes: a P, P -chelate, a P, S -bridged head-to-tail dinuclear complex, and complexes each containing a pair of P -monodentately coordinated P -, P, N - or P, S -ligands. The structures of the ligands and their complexes were determined using 2D NMR spectroscopy. Four diamidophosphites were also characterized via their X-ray structural data. This kind of stereoselector exhibited up to 98% ee in the Pd-mediated allylic substitution of ( E )-1, 3-diphenylallyl acetate with C- and N-nucleophiles. In the Pd-catalyzed allylic alkylation of cinnamyl acetate with various C-nucleophiles, ee values of up to 90% were obtained. In addition, up to 71% ee was achieved in the Pd-catalyzed asymmetric amination of 2-(diethoxyphosphoryl)-1-phenylallyl acetate with aniline, which is a pioneering example of diamidophosphite-type ligand involvement in this challenging reaction. The effects of the diamidophosphite moiety and the denticity of the ligands on the catalytic activity and enantioselectivity were investigated.